2020
DOI: 10.1111/jocs.14438
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement 24 years after cardiac transplantation

Abstract: As patient survival after cardiac transplantation has improved over the course of the last several decades, clinicians are now faced with late complications. This includes aortic stenosis which, traditionally, has been treated with reoperative sternotomy and aortic valve replacement. Transcather aortic valve replacement (TAVR) offers a minimally invasive alternative in this high‐risk population. A small but growing number of cases of TAVR after heart transplantation in high‐risk patients have been reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Furthermore, it has been indicated that there was insufficient information about the surgical treatment of late complications after heart transplantation. [ 15 ] Normally, a contraindication to harvest a graft is the presence of any echocardiographic valvular changes, and yet, valve procedures can be performed on marginal donors before the transplantation, and this can help expand the donor pool without affecting outcomes. [ 16 , 17 ] Moreover, it is well-known that valvular dysfunction following cardiac transplantation is not as frequent as CAV, a condition that is responsible for long-term graft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it has been indicated that there was insufficient information about the surgical treatment of late complications after heart transplantation. [ 15 ] Normally, a contraindication to harvest a graft is the presence of any echocardiographic valvular changes, and yet, valve procedures can be performed on marginal donors before the transplantation, and this can help expand the donor pool without affecting outcomes. [ 16 , 17 ] Moreover, it is well-known that valvular dysfunction following cardiac transplantation is not as frequent as CAV, a condition that is responsible for long-term graft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[30] In addition, AS is identified in 11 patients in this review. [6,15,[31][32][33][34][35][36][37][38] Two of the patients underwent cardiac transplantation with a graft that has bicuspid aortic valve. [31,38] Bicuspid aortic valve is the most common congenital valvular abnormality in which only two cusps of the aortic valve are present since the separation of valve cusps does not happen in the fetal period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, organ recipients have begun receiving TAVR with good results. TAVR has been described in heart transplant patients as early as 2010 [ 1 ], and has been attempted at increasing intervals from the original transplant, with cases showing success at 9 [ 1 ], 14 [ 2 ], and greater than 20 years after transplant in patients with aortic stenosis [ 3 , 4 ]. Similarly, TAVR has begun to be used off-label to treat aortic insufficiency in similar patient populations with good results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%